A pH-Sensitive Fluor, CypHerTM 5, Used to Monitor Agonist-Induced G Protein-Coupled Receptor Internalization in Live Cells - E.J. Adie; S. Kalinka; L. Smith; M.J. Francis; A. Marenghi; M.E. Cooper; M. Briggs; N.P. Michael; G. Milligan; S. Game (BioTechniques)
G protein-coupled receptors (GPCRs) are the largest family of proteins involved in transmembrane signal transduction and are actively studied because of their suitability as therapeutic small-molecule drug targets. Agonist activation of GPCRs almost invariably results in the receptor being desensitized. One of the key events in receptor desensitization is the sequestration of the receptor from the cell surface into acidic intracellular endosomes. Therefore, a convenient, generic, and noninvasive monitor of this process is desirable. A novel, pH-sensitive, red-excited fluorescent dye, CypHerTM 5, was synthesized. This dye is non-fluorescent at neutral pH and is fluorescent at acidic pH. Anti-epitope antibodies labeled with this dye were internalized in an agonist concentration- and time-dependent manner, following binding on live cells to a range of GPCRs that had been modified to incorporate the epitope tags in their extracellular N-terminal domain. This resulted in a large signal increase over background. When protonated, the red fluorescence of CypHer 5 provides a generic reagent suitable for monitoring the internalization of GPCRs into acidic vesicles. This approach should be amenable to the study of many other classes of cell surface receptors that also internalize following stimulation.